Prevalence of Staphylococcus Aureus Nasal Carriers Among Food Handlers and in Selected Food and its Association with Knowledge, Attitude and Practice - Abdul Mutalib, Noor Azira (2011)
The outbreak of food poisoning due to Staphylococcus aureus has been reported with a significant level of morbidity worldwide. The outbreaks occur due to lack of proper food handling practices by the food handling personnel. In this study, the prevalence of S. aureus nasal carriage as well as their knowledge, attitude and practice (KAP) were determined among food handlers and its association with the gender, age, work duration, educational level and food premises. 128 samples taken from nasal swabs of 64 food handlers’ and 64 food items were collected and analyzed. Furthermore during the collection of samples, questionnaire regarding KAP on food hygiene and sanitation were also distributed among the food handlers. The isolates were identified as S. aureus based on colonial morphology, Gram stain, mannitol salt agar fermentation, catalase and coagulase test. Antibiotic susceptibility profiles of the isolates were also done in order to study the resistance pattern of the isolates. Twenty three percent of food handlers were found to be positive for S. aureus nasal carriage and 37.5% of the food samples were contaminated with an average of 8.4 x 106 CFU/g. None of the isolates was resistant to oxacillin and mupirocin but most of the isolates (74.4%) were resistant to penicillin. Only 15.4% and 5.1% of the isolates were resistant to tetracycline and erythromycin, respectively. In addition, seven antibiotic profiles were determined from the antibiotic susceptibility test. The mean score (SD) of the food handlers’ knowledge, attitude and practice were 83.98% (13.26), 82.8% (10.94) and 77.04% (14.98) respectively. Premise grades C proves to be a significant predictor for food handlers knowledge [OR 21.0, (95% CI = 3.522-125.219, P value = 0.001)]. In addition, knowledge on food hygiene and sanitation showed a significant association with attitude [OR 10.0, (95% CI = 1.988-50.291, P value = 0.005)]. The result for attitude section also showed that food handlers with diploma proves to be a significant predictor for attitude [OR 7.9, (95% CI = 1.890-32.905, P value = 0.005)]. Moreover, knowledge on food hygiene and sanitation showed a significant association with practice [OR 18.3, (95% CI = 1.440-23.408, P value = 0.005)]. However sociodemographic dharacteristic and food handlers’ KAP have no significant association with food handlers carrier status. The result shows that even though the KAP level of food handlers were excellent, more than 20% of them were S. aureus nasal carriers and the number of contaminated food was also high. Thus, improvement in hygiene and sanitation is needed.